Enhancement of soil thermo-physical properties using microencapsulated phase change materials for ground source heat pump applications - Dehdezi, Pejman Keikhaei; Hall, Matthew R.; Dawson, Andrew (Trans Tech Publications, 2011)
Soil can be modified with Phase Change materials (PCM) in order to enhance its thermophysical properties and energy storage for ground source heat pump applications. This paper studies thermo-physical properties of soil modified with different amount of microencapsulated PCM. It is shown that increasing PCM amount in soil lead to lower thermal conductivity and increase of volumetric heat capacity of PCM-modified soil across the PCM melting temperature range. In addition, numerical simulation is performed to study the potential application of PCM modified soil for reduction of temperature variations in ground. The result of numerical simulation revealed that temperature variation under PCM-modified soil can be reduced by up to 3ºC compared to conventional soil.